Determinants of entrepreneurial intentions in European sports science students: Towards the development of future sports entrepreneurs - María Huertas González-Serrano; Irena Valantine; Radenko Matić; Ivana Milovanović; Ruslana Sushko; Ferran Calabuig (European Research on Management and Business Economics (ERMBE), 2023)
This study aims to analyse the determinants of sport science students' entrepreneurial intentions considering the cultural effect on these relationships. The sample comprises 764 final-year sport science students from five European countries: Lithuania, Spain, Ukraine, Serbia, and Croatia. A validated structured questionnaire was used to collect the data. The results showed significant direct effects between attitude towards behaviour and perceived behavioural control in sport science students' entrepreneurial intentions in all countries. Entrepreneurial skills presented an indirect impact (through attitude and perceived behavioural control) on all countries' entrepreneurial intentions. However, the importance of each of these variables in explaining entrepreneurial intentions varied according to the students' national culture. This study presents a series of educational policy implications to improve sports science students' employability by developing their entrepreneurial spirit.
Keywords: I23; L26; M13; 650; Sport entrepreneurship; European countries; Higher education; Employability